PENYULUHAN HIGIENE DAN SANITASI PADA SDM PRODUKSI USAHA KECIL OBAT TRADISIONAL (UKOT) PT.GRANINDO JAYA MAKASSAR - Suhartini; Wahyuni, Yuyun Sri; Tahir, Muhammad; Ramadani, Ananda (Akademi Farmasi Yamasi Makassar, 2023)
Outreach is an activity to educate individuals or groups, providing knowledge, information and various abilities to shape proper attitudes and behavior in life. The traditional medicine industry must pay attention to the safety of the products produced, such as implementing sanitation and hygiene. Education regarding sanitation and hygiene in industry is very important to avoid product contamination so that it is safe and suitable for consumption. This activity aims to provide understanding to human resources to behave hygienically to eliminate all potential sources of contaminants and cross-contamination from various sources which pose a risk to product quality. This community service activity takes the form of delivering knowledge and skills improvement material to UKOT PT Granindo Jaya Makassar human resources regarding the application of sanitation and hygiene according to CPOTB in the process of handling basic materials, processing and packaging methods. To evaluate this activity, a pre-test was given before delivering the material and a post-test after delivering the material. From the results of the activities, this extension is proven to increase knowledge and skills so that the traditional products that will be produced always meet the quality requirements that have been determined according to their intended use. Improving the quality of traditional medicines produced and marketed will provide guarantees of quality, efficacy and safety for traditional medicine consumers, especially consumers of PT Granindo Jaya Makassar products